Serupa tapi tak sama: Analisis Perbandingan Guide arsip statis dan Penerbitan Naskah Sumber Arsip: Array - Dharwis Widya Utama Yacob (Arsip Nasional Republik Indonesia, 2013)
Guides and archival publication are two kinds of finding aids having different forms and function. Nevertheless, users still don’t know the function and use. Moreover, archivists still do not understand their differences. Guides are a part of arrangement and description including information and finding aids arrangement. The outputs of arrangement and description activity are archives register, inventory, and guides. The first two are already well known by users and archivists. On the other hands, a guide is still less familiar as a list of archives and inventory. A guide is a process of describing archives comprehensively intended to deliver information on archives collection for users searching potential archives needed. The information included is the institution’s history connected with the collection, volume, substantial information, and the accessibility of archives. Archival publication is an act and procedure resulted from theprocess of the publications of archives by exploring the archives having information on certain topics and published as a book enclosing potential archives. The potential archives should be published like the original one with a notation or a note in order to make the archives more understandable contextually. Beside that, archival publication or bronnen publicatie is a published work containing certain topics of all material derived from archives.